Guidelines for Follow-Up of Women at High Risk for Inherited Breast Cancer: Consensus Statement from the Biomed 2 Demonstration Programme on Inherited Breast Cancer. Issue 1 (17th June 2013) - Møller, P.; Evans, G.; Haites, N.; Vasen, H.; Reis, M. M.; Anderson, E.; Apold, J.; Hodgson, S.; Eccles, D.; Olsson, H.; Stoppa-Lyonnet, D.; Chang-Claude, J.; et al.
Abstract : Protocols for activity aiming at early diagnosis and treatment of inherited breast or breast-ovarian cancer have been reported. Available reports on outcome of such programmes are considered here. It is concluded that the ongoing activities should continue with minor modifications. Direct evidence of a survival benefit from breast and ovarian screening is not yet available. On the basis of expert opinion and preliminary results from intervention programmes indicating good detection rates for early breast cancers and 5-year survival concordant with early diagnosis, we propose that women at high risk for inherited breast cancer be offered genetic counselling, education in 'breast awareness' and annual mammography and clinical expert examination from around 30 years of age. Mammography every second year may be sufficient from 60 years on. BRCA1 mutation carriers may benefit from more frequent examinations and cancer risk may be reduced by oophorectomy before 40–50 years of age. We strongly advocate that all activities should be organized as multicentre studies subjected to continuous evaluation to measure the effects of the interventions on long-term mortality, to match management options more precisely to individual risks and to prepare the ground for studies on chemoprevention.